2023
DOI: 10.1177/02683555231181858
|View full text |Cite
|
Sign up to set email alerts
|

Saphenous vein aneurysms characterization and treatment: A 36-year single center experience

Abstract: Background Superficial vein aneurysms (SVA) are rare vascular pathologies associated with trauma, chronic venous disease, and venous malformation. Method We retrospectively reviewed cases of SVA treated from 1986 to 2022. Results Out of 2463 venous procedures, 16 patients were found with 19 GSV and 1 SSV aneurysms, with 88% presenting with a palpable mass. Varicose veins were noted in 94% of patients, 81% had concomitant reflux, 15% had thrombus within the aneurysm sac, and 19% demonstrated multiple aneurysms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In a retrospective study of 2463 cases of VA treated between 1986 and 2022, 20 superficial VAs were identified in 16 patients, 19 involving the GSV, and only 1 involving the SSV. 10 Small saphenous vein's aneurysms have been reported, ultimately, only in 41 patients. 1,3,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] As in our report, the aneurysm was located close to the SPJ, with the inferior neck still in the upper third of the SSV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study of 2463 cases of VA treated between 1986 and 2022, 20 superficial VAs were identified in 16 patients, 19 involving the GSV, and only 1 involving the SSV. 10 Small saphenous vein's aneurysms have been reported, ultimately, only in 41 patients. 1,3,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] As in our report, the aneurysm was located close to the SPJ, with the inferior neck still in the upper third of the SSV.…”
Section: Discussionmentioning
confidence: 99%
“…10 Small saphenous vein's aneurysms have been reported, ultimately, only in 41 patients. 1,3,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] As in our report, the aneurysm was located close to the SPJ, with the inferior neck still in the upper third of the SSV. This almost exclusive location is consecutive to the insufficiency of the SPJ's terminal valve, combined with the preserved continence of the pre-terminal valve, which induces an increased pressure in the inter-valvular segment and localised parietal dilatation.…”
Section: Discussionmentioning
confidence: 99%